Occupational mechanical exposures as risk factor for chronic low-back pain: a systematic review and meta-analysis - Jahn, Alexander; Andersen, Johan Hviid; Christiansen, David Høyrup; Seidler, Andreas; Dalbøge, Annett (Scandinavian journal of work, environment & health, 2023)
OBJECTIVES: The association between occupational mechanical exposures and low-back pain (LBP) has been studied in several systematic reviews. However, no systematic review addressing chronic LBP exists. The aim of this systematic review and meta-analysis was to examine the association between occupational mechanical exposures and chronic LBP. METHODS: The study was registered in PROSPERO. We used an existing systematic review to identify articles published before January 2014. For studies published between January 2014 and September 2022, a systematic literature search was conducted in six databases. Two authors independently excluded articles, extracted data, and assessed risk of bias and level of evidence (GRADE). Meta-analyses were conducted using random-effects models comparing highest versus lowest exposure group with sensitivity analyses based on study quality (low/moderate versus high risk of bias), study design (cohort versus case–control), and outcome definition (non-specific LBP versus specific chronic LBP). RESULTS: Twenty-six articles were included. Highest pooled odd ratios (OR) were found for combined mechanical exposures [OR 2.2, 95% confidence interval (CI) 1.4–3.6], lifting/carrying loads (OR 1.7, 95% CI 1.4–2.2), and non-neutral postures (OR 1.5, 95% CI 1.2–1.9). For the remaining mechanical exposures (ie, whole-body vibrations, standing/walking, and sitting), OR ranged between 1.0 and 1.4. In the sensitivity analyses, generally, higher pooled OR were found in low/moderate risk of bias studies, case–control studies, and studies of specific chronic LBP. CONCLUSIONS: Moderate evidence of an association was found for lifting/carrying loads, non-neutral postures, and combined mechanical exposures. Low or very low evidence was found for whole-body vibrations, standing/walking, and sitting. Studies using standardized exposure definition, metric, and technical measurements are highly warranted.